The Selection of an E-Wallet by Mathematics Students at the University of North Sumatra Using the Analytical Hierarchy Process (AHP) Method - Siringoringo, Yan Batara Putra; Tiovanny, Angel; Waruwu, Cindy Berlianti; Simanjuntak, Jelita Octavia (Journal of Research in Mathematics Trends and Technology, 2023)
Choosing an e-wallet is an important decision for students at the University of North Sumatra (USU) because it affects their financial management. The Analytical Hierarchy Process (AHP) method is used to evaluate and compare available e-wallets based on criteria that are relevant to students. This method allows students to determine the e-wallet that best suits their needs and priorities. This study shows that AHP is a useful tool to help students choose the right e-wallet.Keyword: e-wallet, management, Analytical Hierarchy Process, priorities